Program of Community Service in Improving Children's Ability to Quran Recitation in Petuaran Hilir Village - Neliwati Neliwati; Nazmi Wiki Kartika Nazmi; Mayanda Firly; Muhammad Sendi; Syafiratunnisa Nasution (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This study seeks to examine student participation in improving the ability to read the Qur'an for children in community service activities in the village of Petuaran Hilir. In encouraging the improvement of reading the Qur'an for children alone, as can be seen how the cultivation of reading is starting to become extinct in the current era, therefore it is necessary to cultivate it again to be diligent in reading, for that in this study it will be explained as to the right thing to increase a high level of interest in reading both in the field of religion and in the general field. In this study using the method of library research. The method is a process that has participation, together ness and involvement in both community groups or individual communities or social institutions based on public awareness directly or indirectly and does not have coercion from certain parties. The result of the study are obtains research data, here the researcher collects, analyze, on participant and reading the Quran.